Local heat transfer coefficients on flat continuous, flat interrupted and corrugated external cooling fins - Robertson, A; Neely, A; Ireland, P; Harper, L (ASME, 1997)
An experimental investigation into the performance of gas turbine engine component external cooling fins has been carried out using the transient liquid crystal technique in a low speed wind tunnel. Full fin surface local heat transfer coefficient distributions have been determined. Measurements with this level of resolution are not previously reported in the literature. In addition to the flat continuous fins, interrupted and corrugated fin geometries have been tested. These geometries enhance heat transfer coefficients by disrupting the thermal and velocity boundary layers which grow down the length of the fin. All geometries are tested at a range of flow speeds and comparisons are made with the relevant literature.